Review article: the key technologies of brain-computer interface. (May 2020) - Cui, Hongmei; Jiang, Qin; Lin, Wenzhang; Liu, Xiujun
Abstract: As an important branch of intelligent robots, brain-computer interface (BCI) technology has great application prospects in the fields of neurological rehabilitation, functional prosthesis assistance and neurological monitoring. Many breakthroughs have been made in the research of brain-computer interface. Based on the existing research literature, this paper has done the following work: outlined the research significance and development status of brain-computer interface technology; introduced the working principle and structure of brain-machine interface system; compared EEG signals of different frequencies, and classified their application fields; analyzed five preprocessing methods, and listed their advantages and disadvantages; summarized the theories and algorithms involved in feature extraction and pattern classifier. Finally, after a detailed introduction of the non-intrusive brain-computer interface components, the paper summarized the current technical challenges faced by the brain-computer interface system.